Job Motivation and Satisfaction Among Female Pharmacists Working in Private Pharmacy Professional Sectors in Saudi Arabia - Al-Omar HA; Khurshid F; Sayed SK; Alotaibi WH; Almutairi RM; Arafah AM; Mansy W; Alshathry S (Dove Medical Press, 2022)
Hussain Abdulrahman Al-Omar,1 Fowad Khurshid,1 Sarah Khader Sayed,1 Wedad Hamoud Alotaibi,1 Rehab Mansour Almutairi,1 Azher Mustafa Arafah,1,2 Wael Mansy,1 Sultan Alshathry3 1Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 2College of Pharmacy, Almaarefa University, Riyadh, Saudi Arabia; 3Ministry of Health, Riyadh, Saudi ArabiaCorrespondence: Hussain Abdulrahman Al-Omar, Department of Clinical Pharmacy, College of Pharmacy, King Saud University, P.O. Box 2457, Riyadh Zip, 11451, Saudi Arabia, Tel +966- 11-4673637, Fax +966 − 11- 4677480, Email halomar@ksu.edu.saBackground: Pharmacists' job satisfaction has been of interest for many years and is of great importance in several respects, such as productivity and ultimately organizational performance.Objective: This study aimed to investigate the perceived motivational factors and levels of job satisfaction of female pharmacists working in private pharmaceutical sectors.Methods: This was a cross-sectional study using a web-based survey of randomly selected female pharmacists working in different private settings including community pharmacies, pharmaceutical companies, private hospitals, and other private sectors using a pre-validated satisfaction scale (Warr-Cook-Wall scale).Results: A total of 232 female pharmacists participated in the study with a mean age of 26.1± 2.4 years. Of the total respondents, more than half (58%) worked for pharmaceutical companies, 25% worked in community pharmacies, and 16.8% were from hospital pharmacies. The most attractive motivating factors that encourage female pharmacists toward better performance were having the opportunity to learn new skills, being in contact with people both locally and internationally, gaining a sense of achievement, and being recognized, appreciated, and rewarded. The participants of this study were shown to have a moderate job satisfaction level.Conclusion: This study revealed that the non-Saudi, part-time pharmacists who never expected a promotion were less satisfied than the Saudi, full-time employees who expected a promotion within a year.Keywords: motivation, satisfaction, female, job, pharmacists, Saudi Arabia